The girl who turned into a fish and other classic Philippine water tales - Paterno, Maria Elena; Gamos, Albert (Manila: Tahanan Books for Young Readers, 1997)
Eight classic water tales from the Philippines tell the story of why the sea is salty, how waterfalls came to be, how a girl turned into a mermaid, and of human interactions-- punishments for vanity, rewards for humility, and the triumph of the underdog.
Primary
Keywords: Tales -- Philippines; Folklore -- Philippines